The impact of modern threats on the national security and safety structure A view on small states' critical infrastructures in security, economic and social regards - Kraus Andreas (2017)
In general, the research fields of the thesis represent the topic's ground work. For this work there are two dominating research fields. These are economic research and security research. They were chosen due to the fact, that all of the selected topics show a significant outcome to these research fields. Another reason for the focus on economic and security issues was the requirement of the course of studies. In addition to the primary fields, some secondary research fields/areas are respected, too. They represent side gains and aspects from the processing of the main topics and have few to middle influence on the research result. Within the next parts of this chapter the main research fields will be described. The intersections between the most important topics of the main part can be seen in figure 2, which also illustrates that there are several overlapping thematic areas. It also symbolizes the percentage, the topic takes part in the certain field.